Peran Hukum dalam Menjamin Akses Pendidikan Inklusif melalui Kebijakan Publik - Novaranti Zura Dwiputri; Ismarini Della Purnama; Ahmad Ahsin Thohari (International Forum of Researchers and Lecturers, 2025)
Inclusive education is an integral part of human rights guaranteed by the constitution and strengthened through various national regulations and international legal instruments. This article aims to analyze the role of law in ensuring access to inclusive education in Indonesia and examine the effectiveness of the implementation of law-based public policies in this field. Using a normative-juridical approach, this study examines legal provisions such as the 1945 Constitution, Law No. 8 of 2016, and Permendiknas No. 70 of 2009, and examines the challenges of implementation at the regional level. The results of the analysis show that although the legal framework is available, the implementation of inclusive education policies still faces various structural, juridical, and cultural obstacles, such as the lack of special tutors, weak supervision, and the lack of synchronization between central and regional policies. Therefore, inclusive, evaluative, and participatory legal policy reforms are needed to realize fair and equal education for all citizens, especially vulnerable groups.